Mitchell's Advanced building construction : the structure - Foster, J. Stroud (London : B.T. Batsford, 1963)
The scope of this book is to provide a two dimensional approach to construction. Volume one will discuss the structure and cascassing of building while the second volume would deal with the components, services and finishes. A new edition of the first volume of ... Mitchell's Advanced building construction which is now published in two parts (the companion volume entitled The structure).
Include bibliographical footnotes and index.
asm 22/01/2019
Loans
Keywords: Building